Coupled Coincidence Points of Mappings in Ordered Partial Metric Spaces - Zorana Golubović; Zoran Kadelburg; Stojan Radenović (Abstract and Applied Analysis)
New coupled coincidence point and coupled fixed point results in ordered partial metric spaces under the contractive conditions of Geraghty, Rakotch, and Branciari types are obtained. Examples show that these results are distinct from the known ones.